Successful management of a spontaneous viable monochorionic diamniotic twin pregnancy on cesarean scar with systemic methotrexate: A case report. Issue 37 (September 2018) - Baradwan, Saeed; Khan, Faryal; Al-Jaroudi, Dania
Abstract: Rationale: Cesarean scar twin pregnancy is exceedingly rare and it remains to be a life-threatening condition even in the early weeks of gestation. Because of its rare occurrence, there is no consensus on the treatment modality of cesarean ectopic pregnancy. Patient concerns: A 41-year-old, woman, gravida 7, para 6, with a history of low transverse cesarean section 2 years back presented with an estimated 6 weeks gestational age and viable spontaneous twin, monochorionic diamniotic gestation. The patient presented to the Emergency Department with complaints of vaginal bleeding and mild lower abdominal pain for 5 days. Diagnoses: An ultrasound examination was performed demonstrating a single intrauterine gestational sac with 2 viable embryos (monochorionic diamniotic) implanted in the lower uterine segment at the level of the prior cesarean section scar. A diagnosis of viable cesarean scar twin pregnancy was made. Interventions: A 2 doses of 50 mg/m 2 methotrexate (MTX) was given intramuscularly. The response to the treatment was monitored by serial beta-human chorionic gonadotropin (β-hCG) and ultrasound. Outcomes: Patient was followed up with β-hCG weekly levels which became 0 after 68 days of treatment. During the follow-up, the patient was asymptomatic, no side effects of MTX were noticed. Lessons: We reported a rare case of viable monochorionic diamniotic twin pregnancy on a cesarean scar that was successfully treated with systemic MTX without any additional therapy. Additionally, the decline of β-hCG in twin ectopic cesarean scar pregnancy appears to be similar to a singleton ectopic pregnancy.